MAKNA SIMBOLIK BUSANA TARI BARONGAN SODO INTERPRETASI ETNOKOREOLOGI TERHADAP NILAI TRADISI LOKAL - Raditya Reyfa Erlangga; I Nengah Mariasa; Enie Wahyuning Handayani; Ni Luh N. Jeylita Paramacitha (Institut Seni Indonesia Surakarta, 2025)
In traditional dance performances, costume serves not merely as a visual complement but as a symbolic medium through which cultural values and collective worldviews are articulated. Tari Barongan Sodo emerges as a traditional performing art rooted in an agrarian and religious cultural setting, closely connected to local mythological and cosmological beliefs. The costume elements employed in Tari Barongan Sodo embody symbolic meanings that reflect the Sodo philosophy; nevertheless, interpretations of these symbols have predominantly remained oral and descriptive in nature. This research seeks to examine the symbolic meanings embedded in the Tari Barongan Sodo costume and to analyze their relationship with local traditional values using an ethnocoreological perspective. A qualitative descriptive approach is applied, with data gathered through performance observation, in-depth interviews with artists and cultural figures, and documentation. The data are analyzed inductively by contextualizing the visual characteristics of the costume within the socio-cultural and belief systems of the supporting community. The findings indicate that the Tari Barongan Sodo costume constitutes an integrated system of cultural symbols. The jamang pilis signifies power and the radiance of inner energy, the gimbalan symbolizes freedom and natural strength, the binding ropes and belt represent self-control, and the cawet trousers convey courage and honesty in expressing one’s true identity. Ultimately, the costume functions as a cultural text that conveys cosmological, ethical, and spiritual values and plays an essential role in transmitting local traditional values through performance practice.